Rab35 regulates insulin secretion via phogrin in pancreatic β cells. (20th September 2021) - Lu, Chunting; Zhao, Qingtong; Wang, Dan; Feng, Yunlu; Feng, Lie; Li, Zejian; Shi, Qiping
Abstract: Dysfunction of pancreatic β cell insulin secretion is related to the pathogenesis of type 2 diabetes (T2D). Rab proteins have been shown to be key players in insulin secretion by pancreatic β cells, and phogrin is a marker for the processes of exocytosis and insulin secretion. The purposes of this study were to clarify the regulatory role of Rab35 in insulin secretion and analyse the Rab35/phogrin interaction mechanism in β‐TC‐6 cells. We studied the effects of Rab35 gene overexpression and interference on insulin secretion and phogrin expression and levels in β‐TC‐6 cells. The Rab35/phogrin interaction was verified by GST pulldown, co‐IP and co‐localisation experiments. Here, we report that Rab35 is mainly distributed in the β‐TC‐6‐cell plasma membrane and cytoplasm. Rab35 overexpression promotes insulin secretion and decreases phogrin expression in β‐TC‐6 cells, whereas its silencing significantly inhibits insulin secretion, promotes phogrin expression ( p  < 0.05) and causes phogrin redistribution. Furthermore, Rab35 silencing suppresses exocytosis of insulin. Rab35 interacts with phogrin, and both proteins co‐localise in the plasma membranes and cytoplasm of β‐TC‐6 cells. Our study presents novel evidence that Rab35 regulates insulin secretion by inhibiting phogrin expression and causing intracellular phogrin redistribution in pancreatic β cells. Abstract :